Crosslinkable resin composition and electric wire / cable
The crosslinkable resin composition, using ethylene homopolymer, dicumyl peroxide, TAIC, and α-methylstyrene dimer, addresses the dual challenges of scorch resistance and heat deformation resistance in crosslinked products, achieving superior performance.
Patent Information
- Application Number
- JP2021107237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-29
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-06-29
AI Technical Summary
Conventional crosslinkable resin compositions for insulated electric wires and cables fail to achieve both sufficient scorch resistance and heat deformation resistance in their crosslinked products.
A crosslinkable resin composition comprising high-pressure low-density ethylene homopolymer, dicumyl peroxide as a crosslinking agent, TAIC or TAC as a first crosslinking aid, and α-methylstyrene dimer as a second crosslinking aid, in specific mass ratios, to enhance both scorch resistance and heat deformation resistance.
The composition achieves crosslinked products with excellent scorch resistance and heat deformation resistance, as demonstrated by specific evaluation methods.
Smart Images

Figure 0007619749000002 
Figure 0007619749000003 
Figure 0007619749000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a crosslinkable resin composition containing an ethylene-based resin, and to an electric wire or cable comprising a crosslinked product of the resin composition formed on a conductor as an insulating coating layer. [Background technology]
[0002] Insulated electric power wires and cables are usually produced by coating a conductor with a crosslinkable resin composition by extrusion processing, and then crosslinking the composition to form an insulating coating layer. Here, the crosslinkable resin composition used in the insulating coated electric wire / cable is required to have scorch resistance, heat deformation resistance of the crosslinked product, and the like.
[0003] As a crosslinkable resin composition used for insulating coated electric wires and cables, Patent Document 1 listed below discloses a polymer composition containing an ethylene-based polymer, an organic peroxide, and a polyallyl crosslinking auxiliary. In Patent Document 1, an attempt is made to improve scorch resistance by using a polyallyl crosslinking auxiliary and reducing the content of the organic peroxide, which is a crosslinking agent, but a sufficient improvement effect is not obtained.
[0004] Patent Document 2 listed below discloses a composition containing an ethylene-based polymer, an organic peroxide such as dicumyl peroxide, a dielectric fluid such as alkylated naphthalene, and a cross-linking coagent such as α-methylstyrene dimer. A crosslinking aid such as α-methylstyrene dimer is said to improve the scorch resistance of the resulting composition and also improve the cured state of the crosslinked product of the composition. However, the crosslinked product of the composition described in Patent Document 2 does not have sufficient heat distortion resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-7013 A [Patent Document 2] Special Publication No. 2015-535864 Summary of the Invention [Problem to be solved by the invention]
[0006] Conventionally known crosslinkable resin compositions, including the compositions disclosed in Patent Document 1 and Patent Document 2, are not satisfactory in both scorch resistance and heat distortion resistance of the crosslinked product. Crosslinked products made from resin compositions with good scorch resistance have poor heat distortion resistance, and resin compositions that can be molded into crosslinked products with good heat distortion resistance tend to have poor scorch resistance.
[0007] The present invention has been made based on the above circumstances. An object of the present invention is to provide a crosslinkable resin composition which is capable of giving a crosslinked product having good scorch resistance and excellent resistance to thermal distortion. [Means for solving the problem]
[0008] The crosslinkable resin composition of the present invention comprises Made of high-pressure low-density ethylene homopolymer It is characterized by containing 100 parts by mass of an ethylene-based resin (A), 0.85 to 1.25 parts by mass of a crosslinking agent (B) made of an organic peroxide, 0.07 to 0.60 parts by mass of a first crosslinking aid (C1) made of an allyl group-containing compound, and 0.15 to 0.38 parts by mass of a second crosslinking aid (C2) made of an α-methylstyrene dimer.
[0009] In the crosslinkable resin composition of the present invention, it is preferred that the crosslinking agent (B) is dicumyl peroxide, and the first crosslinking aid (C1) is TAIC or TAC, particularly TAIC.
[0010] In the crosslinkable resin composition of the present invention, the mass ratio of the second crosslinking aid (C2) to the first crosslinking aid (C1) is preferably 0.4 to 2.5.
[0011] The crosslinkable resin composition of the present invention preferably contains 0.90 to 1.20 parts by mass of a crosslinking agent (B) made of dicumyl peroxide, 0.10 to 0.55 parts by mass of a first crosslinking auxiliary (C1) made of TAIC or TAC, and 0.15 to 0.35 parts by mass of a second crosslinking auxiliary (C2).
[0012] The crosslinkable resin composition of the present invention preferably contains 0.91 to 1.16 parts by mass of a crosslinking agent (B) made of dicumyl peroxide, 0.11 to 0.52 parts by mass of a first crosslinking auxiliary (C1) made of TAIC or TAC, and 0.16 to 0.35 parts by mass of a second crosslinking auxiliary (C2).
[0013] The electric wire / cable of the present invention is characterized in that a conductor is covered with an insulating covering layer formed by crosslinking the crosslinkable resin composition of the present invention. Effect of the Invention
[0014] The crosslinkable resin composition of the present invention has good scorch resistance, and by crosslinking it, a crosslinked product having excellent heat distortion resistance can be obtained. [Brief description of the drawings]
[0015] [Figure 1] FIG. 3 is a graph showing the relationship between the content of a first crosslinking aid and the physical properties of the resulting resin composition. [Diagram 2] FIG. 4 is a graph showing the relationship between the content of a second crosslinking aid and the physical properties of the resulting resin composition. [Diagram 3] FIG. 2 is a graph showing the relationship between the content of a crosslinking agent and the physical properties of the resulting resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below. <Crosslinkable resin composition> The crosslinkable resin composition of the present invention contains an ethylene-based resin (A), a crosslinking agent (B) made of an organic peroxide, a first crosslinking aid (C1) made of an allyl group-containing compound, and a second crosslinking aid (C2) made of an α-methylstyrene dimer.
[0017] <Ethylene-based resin (A)> The ethylene-based resin (A) constituting the crosslinkable resin composition of the present invention is made of a high pressure low density ethylene homopolymer.
[0018] High pressure low density ethylene alone The polymer can be produced by a conventional method. can.
[0019] As a polymerization catalyst used in the production of ethylene-based resin (A) is an organic peroxide Examples of the radical generating catalyst include azo compounds and oxygen. can.
[0021] A suitable ethylene-based resin (A) is one having a density of 0.91 to 0.94 g / cm 3 , especially 0.915~0.930g / cm 3 and a melt mass flow rate of 0.01 to 10 g / 10 min, particularly 0.5 to 5 g / 10 min. You can raise your body.
[0022] If an ethylene-based resin with too low a density is used, the abrasion resistance of the insulating coating layer that is finally formed tends to be poor, whereas if an ethylene-based resin with too high a density is used, the flexibility of the insulating coating layer that is finally formed tends to be poor. Furthermore, an ethylene-based resin with an excessively low melt mass flow rate is poor in processability, while the use of an ethylene-based resin with an excessively high melt mass flow rate tends to reduce the mechanical strength, heat deformation resistance, roundness, etc. of the insulating coating layer that is finally formed.
[0023] <Crosslinking agent (B)> The crosslinking agent (B) constituting the crosslinkable resin composition of the present invention comprises an organic peroxide. Specific examples of the crosslinking agent (B) include di-t-butyl peroxide, 1,1-bis-t-butyl peroxybenzoate, 2,2-bis-t-butyl peroxybutane, t-butyl peroxybenzoate, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butyl peroxyhexane, t-butyl cumyl peroxide, and 2,5-dimethyl-2,5-di-t-butyl peroxyhexyne-3, which can be used alone or in combination of two or more. Among these, dicumyl peroxide is preferred.
[0024] In the crosslinkable resin composition of the present invention, the content of the crosslinking agent (B) is usually 0.85 to 1.25 parts by mass, preferably 0.90 to 1.20 parts by mass, and more preferably 0.91 to 1.16 parts by mass, per 100 parts by mass of the ethylene resin (A).
[0025] If the content of the crosslinking agent (B) is less than 0.85 parts by mass, the crosslinked product of the obtained resin composition will have poor heat distortion resistance (see Comparative Example 5 described later). On the other hand, if this content exceeds 1.25 parts by mass, the scorch resistance of the resulting crosslinkable resin composition will be poor (see Comparative Example 6 described later).
[0026] <First crosslinking aid (C1)> The first crosslinking auxiliary (C1) constituting the crosslinkable resin composition of the present invention comprises an allyl group-containing compound. Specific examples of the first crosslinking aid (C1) include TAIC (triallyl isocyanurate), TAC (triallyl cyanurate), TATM (triallyl trimellitate), etc., which can be used alone or in combination of two or more. Among these, TAIC and TAC are preferred, and TAIC is particularly preferred.
[0027] The first crosslinking auxiliary (C1), when contained in a suitable ratio described later, can promote the crosslinking reaction caused by the crosslinking agent (B) and improve the heat distortion resistance of the obtained crosslinked product.
[0028] In the crosslinkable resin composition of the present invention, the content of the first crosslinking auxiliary (C1) is usually 0.07 to 0.60 parts by mass, preferably 0.10 to 0.55 parts by mass, and more preferably 0.11 to 0.52 parts by mass, per 100 parts by mass of the ethylene-based resin (A).
[0029] When the content of the first crosslinking auxiliary (C1) is less than 0.07 parts by mass, the heat distortion resistance of the crosslinked product of the obtained resin composition becomes poor. On the other hand, if the content exceeds 0.60 parts by mass, the scorch resistance of the resulting crosslinkable resin composition will be poor (see Comparative Example 2 described later).
[0030] <Second crosslinking aid (C2)> The second crosslinking auxiliary (C2) constituting the crosslinkable resin composition of the present invention comprises α-methylstyrene dimer (AMSD). The second crosslinking auxiliary (C2) can improve the scorch resistance of the resin composition by being contained in a suitable ratio described later.
[0031] In the crosslinkable resin composition of the present invention, the content of the second crosslinking auxiliary (C2) is usually 0.15 to 0.38 parts by mass, preferably 0.15 to 0.35 parts by mass, and more preferably 0.16 to 0.35 parts by mass, per 100 parts by mass of the ethylene resin (A).
[0032] When the content of the second crosslinking auxiliary (C2) is less than 0.15 parts by mass, the scorch resistance of the obtained crosslinkable resin composition becomes poor. On the other hand, if the content exceeds 0.38 parts by mass, the crosslinked product of the obtained resin composition will have poor heat distortion resistance (see Comparative Example 4 described later).
[0033] In the crosslinkable resin composition of the present invention, the mass ratio of the second crosslinking aid (C2) to the first crosslinking aid (C1) is preferably from 0.4 to 2.5, and more preferably from 0.48 to 2.3. If this mass proportion is too small, the resulting crosslinkable resin composition may not have sufficient scorch resistance. On the other hand, if this mass proportion is too large, a crosslinked product having good resistance to thermal distortion may not be obtained from the resulting crosslinkable resin composition.
[0034] <Optional ingredients> In addition to the above-mentioned ethylene-based resin (A), crosslinking agent (B), first crosslinking aid (C1) and second crosslinking aid (C2), the crosslinkable resin composition of the present invention may contain an olefin-based resin other than the ethylene-based resin (A), a stabilizer, various additives and auxiliary materials depending on the intended use within a range that does not impair the properties of the resin composition of the present invention.
[0035] Examples of the olefin resin, which is an optional component, include ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-maleic acid copolymer, ethylene-diene compound copolymer, ethylene-vinyl silane copolymer, maleic anhydride grafted ethylene polymer, acrylic acid grafted ethylene polymer, and silane grafted ethylene polymer.
[0036] Specific examples of the optional stabilizer (light stabilizer, antioxidant, processing stabilizer) include hindered amine type light stabilizers such as tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate (LA-52 manufactured by ADEKA), 2,2,6,6-tetramethyl-4-piperidyl methacrylate (LA-87 manufactured by ADEKA), and bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate (LA-77 manufactured by ADEKA, or TINUVIN 770 manufactured by BASF);4,4'-thiobis-(3-methyl-6-t-butylphenol) (Shipro Chemicals, Seenox BCS), 4,4'-thiobis-(6-t-butyl-o-cresol) (Ethanox 736, Ethyl Corporation), tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane (Irganox 1010, BASF), N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl] Hydrazine (Irganox 1024, BASF), 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid (Cyanox 1790, Cytec), 1,3,5-trimethyl-2,4-6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene (Ethanox 330, Albert Corporation), triethylene glycol-bis[3-(3-t-butyl-5 -methyl-4-hydroxyphenyl)propionate] (BASF Irganox 245), 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (BASF Irganox 259), octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (BASF Irganox 1076), N,N'-hexamethylenebis(3,5-di t-Butyl-4-hydroxy-hydrocinnamamide) (BASF Irganox 1098), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene (BASF Irganox 1330), tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate (BASF Irganox 3114), isooctyl-3-(3,5-di-t-butyl-4- hindered phenol type stabilizers such as 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)propionate (Irganox 1135 manufactured by BASF), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane (ADEKA STAB AO-30 manufactured by Asahi Denka), 4,4'-butylidenebis-(3-methyl-6-t-butylphenol (ADEKA STAB AO-40 manufactured by Asahi Denka), and 2,2'-thiobis-(4-methyl-6-t-butylphenol);Examples of such stabilizers include dialkylthiodipropionate stabilizers such as dilauryl thiodipropionate (DLTP "Yoshitomi" manufactured by Yoshitomi Pharmaceutical Co., Ltd.), distearyl thiodipropionate (DSTP "Yoshitomi" manufactured by Yoshitomi Pharmaceutical Co., Ltd.), and dimyristyl thiodipropionate (DMTP "Yoshitomi" manufactured by Yoshitomi Pharmaceutical Co., Ltd.);
[0037] Examples of optional additives and auxiliary materials include processability improvers, dispersants, copper inhibitors, antistatic agents, lubricants, and carbon black.
[0038] The crosslinkable resin composition of the present invention can be prepared by blending the essential components [the ethylene-based resin (A), the crosslinking agent (B), the first crosslinking aid (C1) and the second crosslinking aid (C2)] and the optional components in a predetermined ratio, kneading and granulating the mixture. The crosslinkable resin composition of the present invention is preferably in the form of pellets having an average particle size of about 2 to 7 mm from the viewpoints of ease of feeding into the screw of an extruder, ease of handling, and the like.
[0039] <Wires and cables> The electric wire / cable of the present invention comprises a conductor covered with an insulating coating layer formed by crosslinking the crosslinkable resin composition of the present invention, that is, an insulating coating layer made of a crosslinked product of the resin composition. The electric wire / cable of the present invention can be produced by coating a conductor mainly made of copper or aluminum with the crosslinkable resin composition of the present invention by extrusion processing, and then crosslinking the resulting product to form an insulating coating layer.
[0040] In the case of low-voltage cables, typically, only one layer is coated using a single-layer extruder, whereas in the case of high-voltage cables, a three-layer extruder is used to coat a laminate consisting of a first layer made of the inner semiconductive layer resin composition, a second layer made of the crosslinkable resin composition of the present invention, and a third layer made of the outer semiconductive layer resin composition on a conductor at a temperature equal to or higher than the melting temperature of each resin and lower than the decomposition temperature of the crosslinking agent (B), and then the resin composition is crosslinked by heating to a temperature equal to or higher than the decomposition temperature of the crosslinking agent (B) in an atmosphere of nitrogen, water vapor, silicone oil, molten salt, or the like.
[0041] The electric wire / cable of the present invention is excellent in various properties such as electrical properties (insulating properties of the coating layer) and mechanical properties, and can be stably extruded for a long period of time during its production (extrusion molding process). EXAMPLES
[0042] Examples of the present invention will be described below, but the present invention is not limited to these examples. The ethylene-based resins, crosslinking agents and crosslinking assistants used to produce the resin compositions of the examples and comparative examples are as follows.
[0043] Resin (A-1): High pressure low density ethylene homopolymer, Melt mass flow rate (MFR) = 2.2g / 10min, density 0.922g / cm 3 (Manufactured by ENEOS NUC Corporation)
[0044] · Crosslinking agent (B-1): Dicumyl peroxide
[0045] First crosslinking agent (C1-1): TAIC First crosslinking agent (C1-2): TAC Second crosslinking coagent (C2): AMSD · Crosslinking coagent (C3): TMPTA (trimethylpropane triacrylate)
[0046] <Example 1> According to the formulation shown in Table 1 below, 100 parts by mass of resin (A-1), 1.02 parts by mass of crosslinking agent (B-1), 0.29 parts by mass of first crosslinking aid (C1-1), and 0.25 parts by mass of second crosslinking aid (C2) were mixed for 16 hours while heating at 60°C, and then cooled to room temperature to obtain a crosslinkable resin composition of the present invention.
[0047] <Examples 1 to 7> According to the recipe shown in Table 1 below, the crosslinkable resin composition of the present invention was obtained in the same manner as in Example 1, except that the amount of at least one of the crosslinking agent (B-1), the first crosslinking auxiliary (C1-1), and the second crosslinking auxiliary (C2) was changed.
[0048] <Example 8> A crosslinkable resin composition of the present invention was obtained in the same manner as in Example 2, except that 0.15 parts by mass of the first crosslinking auxiliary (C1-2) was used instead of the first crosslinking auxiliary (C1-1).
[0049] <Comparative Example 1> A comparative crosslinkable resin composition was obtained in the same manner as in Example 2, except that the first crosslinking auxiliary (C1-1) was not used.
[0050] <Comparative Example 2> A comparative crosslinkable resin composition was obtained in the same manner as in Example 1, except that the amount of the first crosslinking auxiliary (C1-1) used was changed to 0.72 parts by mass.
[0051] <Comparative Example 3> A comparative crosslinkable resin composition was obtained in the same manner as in Example 4, except that the second crosslinking auxiliary (C2) was not used.
[0052] <Comparative Example 4> A comparative crosslinkable resin composition was obtained in the same manner as in Example 5, except that the amount of the first crosslinking auxiliary (C2) used was changed to 0.47 parts by mass.
[0053] <Comparative Example 5> A comparative crosslinkable resin composition was obtained in the same manner as in Example 6, except that the amount of the crosslinking agent (B-1) used was changed to 0.76 parts by mass.
[0054] <Comparative Example 6> A comparative crosslinkable resin composition was obtained in the same manner as in Example 7, except that the amount of the crosslinking agent (B-1) used was changed to 1.38 parts by mass.
[0055] <Comparative Example 7> A comparative crosslinkable resin composition was obtained in the same manner as in Example 2, except that 0.15 parts by mass of the crosslinking auxiliary (C3) was used in place of the first crosslinking auxiliary (C1-1).
[0056] <Comparative Example 8> A comparative crosslinkable resin composition was obtained in the same manner as in Example 2, except that 0.20 parts by mass of the crosslinking auxiliary (C3) was used in place of the first crosslinking auxiliary (C1-1).
[0057] The scorch resistance and heat distortion property were evaluated for each of the crosslinkable resin compositions obtained in the above Examples 1 to 8 and Comparative Examples 1 to 8. The evaluation methods are as follows. The results are shown in Table 1 and Figures 1 to 3.
[0058] FIG. 1 shows the relationship between the content of the first crosslinking aid (C1-1) and the physical properties (scorch resistance and heat distortion resistance of the crosslinked product) of the resulting resin composition when the contents of the crosslinking agent (B-1) and the second crosslinking aid (C2) are substantially constant. FIG. 2 shows the relationship between the content of the second crosslinking aid (C2) and the physical properties (scorch resistance and heat distortion resistance of the crosslinked product) of the resulting resin composition when the contents of the crosslinking agent (B-1) and the first crosslinking aid (C1-1) are substantially constant. FIG. 3 shows the relationship between the amount of crosslinking agent (B-1) added and the physical properties (scorch resistance and heat distortion resistance of the crosslinked product) of the resulting resin composition when the contents of the first crosslinking aid (C1-1) and the second crosslinking aid (C2) are substantially constant.
[0059] [Method of evaluating scorch resistance] In accordance with JIS K 6300-2, measurements were performed using a Moving Die Rheometer (MDR) at a test temperature of 140°C for 8 hours. The time ts1 required for the torque to increase by 1.0 dNm from the minimum value was measured. The evaluation criteria were as follows: ts1 of 45 minutes or more was rated as "pass", and ts1 of 45 minutes or less was rated as "fail".
[0060] [Method for evaluating heat deformation (hot set)] The resin composition was press molded (temperature 120°C, preheating pressure 0.5MPa x 5 minutes, pressing pressure 15MPa x 15 minutes) to obtain a crosslinked sheet with a thickness of 1 mm. A dumbbell No. 6 test piece was prepared from the crosslinked sheet obtained, and two benchmark lines were drawn in the center of this test piece (marker distance (L0) = 20 mm). Test piece subjected to 20N / cm in a high temperature atmosphere of 200℃ 2 A tensile load of 150 g / m was applied, the gauge length (L1) was measured after 15 minutes, and the hot set (%) was calculated according to the following formula. The evaluation criteria were as follows: a hot set of 80% or less was rated as "pass", and a hot set of more than 80% was rated as "fail".
[0061] Formula: Hot set (%) = [(L1-L0) / L0] x 100
[0062] [Table 1]
[0063] As shown in Table 1 above, all of the crosslinkable resin compositions obtained in Examples 1 to 8 have good scorch resistance, and all of the crosslinked products thereof have excellent heat distortion resistance. In contrast, the composition according to Comparative Example 2 in which the content of the first crosslinking aid exceeded 0.60 parts by mass, the composition according to Comparative Example 3 in which the second crosslinking aid was not used, and the composition according to Comparative Example 6 in which the content of the crosslinking agent exceeded 1.25 parts by mass all had poor scorch resistance. In addition, the composition according to Comparative Example 1, which did not use the first crosslinking aid, the composition according to Comparative Example 4, which contained more than 0.38 parts by mass of the second crosslinking aid, the composition according to Comparative Example 5, which contained less than 0.85 parts by mass of the crosslinking agent, and the compositions according to Comparative Examples 7 and 8, which contained a crosslinking aid made of an acryloyl group-containing compound instead of the first crosslinking aid, all had poor heat distortion resistance of the crosslinked product.
[0064] Furthermore, from Figures 1 to 3, it can be seen that only by containing the first crosslinking aid (TAIC), the second crosslinking aid (AMSD), and the crosslinking agent (dicumyl peroxide) in specific ranges can a resin composition having good scorch resistance and excellent thermal deformation resistance of the crosslinked product be obtained.
Claims
1. 100 parts by mass of an ethylene-based resin (A) consisting of a high-pressure low-density ethylene homopolymer; 0.85 to 1.25 parts by mass of a crosslinking agent (B) consisting of an organic peroxide; A crosslinkable resin composition comprising: 0.07 to 0.60 parts by mass of a first crosslinking auxiliary (C1) made of an allyl group-containing compound; and 0.15 to 0.38 parts by mass of a second crosslinking auxiliary (C2) made of an α-methylstyrene dimer.
2. the crosslinking agent (B) is dicumyl peroxide, The crosslinkable resin composition according to claim 1, wherein the first crosslinking auxiliary (C1) is TAIC or TAC.
3. The crosslinkable resin composition according to claim 2, characterized in that the first crosslinking auxiliary (C1) is TAIC.
4. The crosslinkable resin composition according to any one of claims 1 to 3, characterized in that a mass ratio of the second crosslinking auxiliary (C2) to the first crosslinking auxiliary (C1) is 0.4 to 2.
5.
5. 0.90 to 1.20 parts by mass of a crosslinking agent (B) consisting of dicumyl peroxide, The crosslinkable resin composition according to claim 1, comprising: 0.10 to 0.55 parts by mass of a first crosslinking auxiliary (C1) consisting of TAIC or TAC; and 0.15 to 0.35 parts by mass of a second crosslinking auxiliary (C2).
6. 0.91 to 1.16 parts by mass of a crosslinking agent (B) consisting of dicumyl peroxide, The crosslinkable resin composition according to claim 1, comprising: 0.11 to 0.52 parts by mass of a first crosslinking auxiliary (C1) consisting of TAIC or TAC; and 0.16 to 0.35 parts by mass of a second crosslinking auxiliary (C2).
7. 7. An electric wire or cable comprising a conductor covered with an insulating covering layer formed by crosslinking the crosslinkable resin composition according to claim 1.
Citation Information
Patent Citations
Cable insulation compositions comprising a phosphorus-containing antioxidant
CN107771197A
Crosslinking composition for ethylene based polymer and crosslinking method
JP1992218546A
Method for crosslinking rubber
JP2004123949A
Method for reducing peroxide migration in crosslinkable ethylene polymer compositions
JP2015535864A
Crosslinkable polymer composition, method for making same, and article made therefrom
JP2019007013A